NILAI MORAL YANG DITEMUKAN DALAM NOVEL LASKAR PELANGI KARANGAN ANDREA HIRATA - Endang Yuliani Rahayu (Universitas Stikubank (UNISBANK) Semarang, 2013)
Novel is an interesting object to explore to get hiddenmessages written in it. As one of literary objects, novel has values containedin the story. The values are varied depend on the genre of the novel. The genrerepresents many elements of a novel, for examaple is the values. Therefore, the writer is interested to investigate the moral values contained in Novel Laskar Pelangi. Laskar Pelangi is a modern novel that tells about the spirit of a veryloyal and devoted teacher, named Ibu Mus, who teaches the students whom arefrom different economical background. There are ten students whoare willing to go to the sameschool called SD Muhammadiyah in a remote arae in Belitong. Since the parents are just the low paid workers, they do not have money to sendtheir children to state school. The local government intends to close the schoolbut because of the fighting from Ibu Mus who insits to keep the school finallythe government is reluctant to let it open.KEY WORDS:moral, values, morality